Effect of temperature, pressure and power in obtaining TiO2 and TiO2-Fe via microwaves and evaluation of photocatalytic activity with synthesis time - Zurita Luna, Ulises; Zárate Medina, Juan; Gallegos Hernández, Anayeli Yazmin; Romero Toledo, Rafael; Cortés, José Apolinar (Acta Universitaria, 2019)
Photocatalysts of titanium dioxide (TiO2) doped with different percentages of iron were synthesized via microwave at 180 °C, with two different times, 2 min and 10 min. Temperature, pressure, and power change were analyzed. Important changes were mainly observed in the pressure conditions. The synthesized photocatalysts were characterized using: Scanning electron microscopy (SEM), X-ray diffraction (XRD), specific surface area (BET), and UV-vis diffuse reflectance spectroscopy. The presence of nanoparticles was observed; furthermore, anatase crystalline phase of TiO2 was the only found. A study of the photocatalytic activity for discoloration acid blue dye 9 (AB9) with UV light was performed, and it was compared with the commercial photocatalyst Degussa P-25, being the best result a total discoloration of dye at 45 min of reaction using the TiO2 photocatalyst undoped synthesized at 2 min. The iron doping did not show an improvement in the photocatalytic activity, and it was also observed that the time of synthesis considerably influences in the photocatalytic activity, with best efficiencies at minor synthesis time.